Pengaruh Kenyamanan, Nilai Yang Dirasakan Dan Kepuasan Pelanggan Terhadap Minat Beli Ulang Pada Pengguna Marketplace Tokopedia - Hafidz, Gilang Pratama; Nabilah, Putri Salma (Jurnal Ilmiah Wahana Pendidikan, 2024)
Repeat purchase intention has become an important supporting aspect in the context of online purchasing to measure the likelihood of consumers making multiple purchases from the same online seller. The aim of this research is to determine the effect of convenience variables on repurchase intention through perceived value and customer satisfaction in the context of online shopping among marketplace users. This type of research is quantitative with a purposive sampling technique which was distributed via questionnaire to 200 marketplace user respondents aged 18 - 55 years in the Bekasi area. The analysis used is the Structural Equation Model (SEM). The results of this research state that the comfort variable has the greatest direct influence on Perceived Value followed by Customer Satisfaction and Repurchase Intention. Then customer satisfaction has the greatest indirect influence on the relationship between comfort and repurchase interest. This research contributes to companies to focus more on the convenience and value perceived by customers. The researcher suggests to future researchers to expand the coverage area of ​​the research area and extend the duration of the research.